Analisis Penggunaan Media Komunikasi Pembelajaran Google Class Room (GCR) Berbasis Teknologi - Dailami Dailami; Sri Rahmayanti (LP. Ma'arif Janggan Magetan, 2024)
The study aims to analyze the use of technology-based Goggle Class Room (GCR) communication media. Qualitative descriptive research method technique with data collection through questionnaires using google forms. The respondents of this study are students in the third (three) semester of the Management study program, Faculty of Economics, Asahan University for the 2023/2024 Academic Year who took the Business Communication course. The number of 50 respondents, representatives of 5 classes. Taken using purposive sampling technique covering 10 people per class. The results showed that the majority of respondents, 64%, said they